2011
DOI: 10.1002/yea.1904
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to thermal and reductive stress in Saccharomyces cerevisiae is amenable to regulation by phosphorylation–dephosphorylation of ubiquitin conjugating enzyme 1 (Ubc1) S97 and S115

Abstract: Ubiquitin conjugating enzyme 1 (Ubc1) is a member of the E2 family of enzymes that conjugates ubiquitin to damaged proteins destined for degradation by the ubiquitin proteasomal system. It is necessary for stress tolerance and is essential for cell survival in Saccharomyces cerevisiae. Ubc1 has five serine residues that are potential substrates for phosphorylation by kinases. However, no data are available to indicate that Ubc1 function or stress tolerance in S. cerevisiae is regulated by serine phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For example, positions that correspond structurally to UbcH5c Asp112 are conserved as either Asp or Ser in a large number of E2s. Yeast E2 Ubc1 Ser115 is a site of reversible phosphorylation associated with a phenotype in which yeast display enhanced tolerance to environmental stresses (Meena et al, 2011). Our E4BU:UbcH5c~Ub model predicts that the phosphorylation of Ubc1 Ser115 would enhance the E2:Ub electrostatic interaction, thereby promoting the activation of Ub transfer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, positions that correspond structurally to UbcH5c Asp112 are conserved as either Asp or Ser in a large number of E2s. Yeast E2 Ubc1 Ser115 is a site of reversible phosphorylation associated with a phenotype in which yeast display enhanced tolerance to environmental stresses (Meena et al, 2011). Our E4BU:UbcH5c~Ub model predicts that the phosphorylation of Ubc1 Ser115 would enhance the E2:Ub electrostatic interaction, thereby promoting the activation of Ub transfer.…”
Section: Discussionmentioning
confidence: 99%
“…UBC is reportedly involved in the tolerance of plants to abiotic stresses, including drought, salt, osmotic and water stress 60 . Previous studies have shown that the tolerance of S. cerevisiae to thermal stress might be regulated by dephosphorylation of the MAP kinase serine residues of UBC1 during exposure to this stress, which leads to increased tolerance to thermal stress 61 . Increases in UBC1 expression and proteasome activity elevated cadmium (Cd) tolerance by reducing the Cd levels through the regulation of Cd transporter expression in NtUBC1 tobacco 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Ubc1, in turn, is involved in protein turnover and essential for survival of yeast cells deleted for UBC4 (Seufert et al, 1990). It was associated with vesicle biogenesis (Shieh et al, 2001), resistance to proteotoxic stress (Meena et al, 2011), transcription factor shuttling (Jiao et al, 2016), and protein quality control in the endoplasmic reticulum (Friedlander, et al, 2000) and in the nucleus (Ibarra et al, 2016). Furthermore, Ubc1 and Ubc4 were shown to act cooperatively in the degradation of substrates of the anaphase-promoting complex (APC/C; Rodrigo-Brenni & Morgan, 2007).…”
Section: Introductionmentioning
confidence: 99%